Utilization of Fruit Seed-Based Bioactive Compounds for Formulating the Nutraceuticals and Functional Food: A Review - Allaqaband, Shumyla; Dar, Aamir Hussain; Patel, Ulpa; Kumar, Navneet; Nayik, Gulzar Ahmad; Khan, Shafat Ahmad; Ansari, Mohammad Javed; Alabdallah, Nadiyah M.; Kumar, Pradeep; Pandey, Vinay Kumar; Kovács, Béla; Shaikh, Ayaz Mukarram (Frontiers in Nutrition, 2022)
Fruit seeds include a large number of bioactive substances with potential applications in the culinary and pharmaceutical industries, satisfying current demands for natural ingredients, which are generally preferred since they have fewer adverse effects than artificial components. Researchers have long been interested in the functional features, as well as the proximate and mineral compositions, of diverse fruit seeds such as tomato, apple, guava, and dates, among others. Bioactive components such as proteins (bioactive peptides), carotenoids (lycopene), polysaccharides (pectin), phytochemicals (flavonoids), and vitamins (-tocopherol) are abundant in fruit by-products and have significant health benefits, making them a viable alternative for the formulation of a wide range of food products with significant functional and nutraceutical potential. This article discusses the role and activities of bioactive chemicals found in tomato, apple, dates, and guava seeds, which can be used in a variety of food forms to cure a variety of cardiovascular and neurological disorders, as well as act as an antioxidant, anticancer, and antibacterial agent. The extraction of diverse bioactive components from by-products could pave the path for the creation of value-added products from the fruit industry, making it more commercially viable while also reducing environmental pollution caused by by-products from the fruit industry.